Exploring the failing right ventricle in pulmonary hypertension by cardiac magnetic resonance: An in vivo study utilizing Macitentan. (2nd September 2022) - Murphy, Gerard; Jayasekera, Geeshath; Mullin, James; Gallagher, Lindsay; Welsh, David J.
Abstract: Cardiac magnetic resonance (CMR) imaging is used to assess the right ventricle (RV) of pulmonary hypertensive (PH) patients and more recently to track changes in response to therapy. We wished to investigate if repeat CMRs could be used to assess ventricular changes in the Sugen 5416 hypoxic (Su/Hx) rat model of PH treated with the dual endothelin receptor antagonist Macitentan. Male Sprague Dawley Su/Hx rats were dosed for 3 weeks with either vehicle or Macitentan (30 mg/kg) daily, control rats received only vehicle. All rats underwent three CMR scans; before treatment, 2 weeks into treatment, and end of the study. A separate group of Su/Hx and control rats, treated as above, underwent terminal hemodynamic measurements. Using terminal and CMR measurements, Macitentan was found to lower RV systolic pressure pulmonary artery remodeling and increase RV ejection fraction but not change RV hypertrophy (RVH). Repeat CMRs determined that Su/Hx rats treated with Macitentan had significantly reversed RVH via reducing RV mass as well as reducing elevated left ventricular eccentricity index; reductions in RV mass were also observed in Su/Hx vehicle rats exposed to normoxic conditions. We have demonstrated that repeat CMRs can be used to assess the volume and structural changes in the ventricles of the Su/Hx rat model. Using repeat CMRs has allowed us to build a more complete picture of the response of the RV and the left ventricle to treatment. It is unknown if these effects are a consequence of direct action on the RV or secondary to improvements in the lung vasculature.